Rat allotransplantation of epigastric microsurgical flaps: a study of rejection and the immunosuppressive effect of cyclosporin A - Carramaschi,Fábio R. (2000)
The rejection of allotransplantation of epigastric microsurgical flaps and the effect of immunosuppression have been studied in 58 rats. Three sets of experiments were planned: (1) Wistar Furth isogenic donors and receptors (control set); (2) Brown Norway donors and Wistar Furth receptors (rejection set); and (3) Brown Norway donors and Wistar Furth immunosuppressed receptors (cyclosporin A set). Cyclosporin A (10 mg/kg/d) treated rats had a transplantation survival rate of up to 30 days: 83.3% among isogenic animals and 60% among allogeneic. There was 100% rejection by the 9th day after the transplantation in allogeneic non-immunosuppressed rats. Biopsies embedded with historesin were taken from the flap and normal contralateral skin (used as control) on the 3rd, 7th, 15th, and 30th days after the surgery. A quantitative study of infiltrating lymphocytes in the flaps, with and without cyclosporin A, was done by evaluating the local inflammatory infiltrate. A significant increase in the number of lymphocytes among the rejection and immunosuppressed groups was seen, as compared to the isogenic set. Local lymphocytosis in allogeneic non-immunosuppressed transplantations reached its highest level on the 3rd day after surgery, before gross findings of rejection, which could only be seen by naked eye on the 5th or 6th day. Therefore, we conclude that cyclosporin A is effective in preserving allogenic transplantation in rats. Biopsies of transplanted areas may contribute to earlier diagnosis of the need for immunosuppressive therapy.